Penyalahgunaan Dana Desa oleh Kepala Desa di Kabupaten Bangkalan: Tinjauan Tahun 2018-2023 - Andika Danang Saputra; Rizqa Noviana Putri; Tegar Catur Kurniawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This abstract provides an overview of the distribution of village funds by village heads in Bangkalan Regency during the 2018-2023 period. This research aims to analyze village fund patterns, the factors that influence them, and their impact on development and the economy in the region. The research methods used include secondary data analysis and surveys of relevant stakeholders, with a focus on transparency in village fund management and future prevention efforts.